FRENCH CLASSICAL THEATRE: SEVENTEENTH-CENTURY DRAMATURGY AND STAGE CULTURE - Kaljanova, Tazakhan (International Conference on Social Sciences & Humanities, 2026)
This article provides a scholarly analysis of the formation of seventeenth-century French Classical theatre, its aesthetic principles, the stages in the development of its dramaturgy, and the distinctive features of its stage culture. It also examines the principal representatives of Classical dramaturgy, their creative legacy, and their contribution to the development of world theatre art. Furthermore, the study presents scientific conclusions regarding the artistic principles of French Classical theatre and its significance in contemporary theatre practice.